2021
DOI: 10.1007/s11356-021-15366-4
|View full text |Cite
|
Sign up to set email alerts
|

Effective adsorptive removal of atrazine herbicide in river waters by a novel hydrochar derived from Prunus serrulata bark

Abstract: In this work, a novel and effective hydrochar was prepared by hydrothermal treatment of Prunus serrulata bark to remove the pesticide atrazine in river waters. The hydrothermal treatment has generated hydrochar with a rough surface and small cavities, favoring the atrazine adsorption. The adsorption equilibrium time was not influenced by different atrazine concentrations used, being reached after 240 min. The Elovich adsorption kinetic model presented the best adjustment to the kinetic data. The Langmuir model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 89 publications
2
7
0
Order By: Relevance
“…The "approximate ΔG 0 " values were negative thus indicating that atrazine sorption in the substrates was favorable under the tested conditions. Our values are more negative than those reported for soils (Alister et al, 2020) and in the same range for values reported for biochar amended soils and hydrochar (Deng et al, 2017;Netto et al, 2022).…”
Section: Characteristics Of the Substratessupporting
confidence: 80%
“…The "approximate ΔG 0 " values were negative thus indicating that atrazine sorption in the substrates was favorable under the tested conditions. Our values are more negative than those reported for soils (Alister et al, 2020) and in the same range for values reported for biochar amended soils and hydrochar (Deng et al, 2017;Netto et al, 2022).…”
Section: Characteristics Of the Substratessupporting
confidence: 80%
“…Non-linear equations of pseudo-first order, pseudo-second order, Elovich, general order and Avrami kinetic models were used to analyze the adsorption kinetics. The equations are described below: where: q t is the crystal violet amount adsorbed at time t ; k 1 , k 2 , k n and k AV are the rate constants of pseudo-first-order, pseudo-second-order, general order and Avrami kinetic models; q e , q n and q AV are the theoretical values for the adsorption capacity; a is the desorption constant of Elovich model; b is the initial velocity; n is the general order exponent and n AV is a fractional exponent [ 18 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…Non-linear equations of Langmuir, Freundlich, Temkin, Sips and Redlich-Peterson isotherms were used to describe the adsorption equilibrium. The corresponding equations are as follows: where: q m and Q sat are the maximum absorption capacities; K L , K F , K T , K S and K RP are the Langmuir, Freundlich, Temkin, Sips and Redlich-Peterson isotherms constants; 1/n F is an empirical constant indicating the intensity of adsorption; R is the universal gas constant; T is the absolute temperature; b is Temkin constant which related to the adsorption heat; n is Sips isotherm exponent; a RP is Redlich-Peterson isotherm constant and β RP is Redlich-Peterson exponent which can vary between 0 and 1 [ 18 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The kinetic and equilibrium data were modeled using the non-linear equations of the pseudo-first-order, pseudo-second-order, Elovich, and Avrami kinetic models and the Langmuir, Freundlich, Temkin, and Sips isotherms, respectively [ 29 , 30 , 31 , 32 , 33 ]. Detailed information about these equations is presented in Supplementary Materials Table S1 .…”
Section: Methodsmentioning
confidence: 99%